Targeting of the Arpc3 actin nucleation factor by miR-29a/b regulates dendritic spine morphology - Lippi, Giordano; Steinert, Joern R.; Marczylo, Emma L.; D’Oro, Sabina; Fiore, Roberto; Forsythe, Ian D.; Schratt, Gerhard; Zoli, Michele; Nicotera, Pierluigi; Young, Kenneth W. (The journal of cell biology, 2011)
Previous studies have demonstrated that microribonucleic acids (miRs) are key regulators of protein expression in the brain and modulate dendritic spine morphology and synaptic activity. To identify novel miRs involved in neuronal plasticity, we exposed adult mice to chronic treatments with nicotine, cocaine, or amphetamine, which are psychoactive drugs that induce well-documented neuroadaptations. We observed brain region- and drug-specific changes in miR expression levels and identified miR-29a/b as regulators of synaptic morphology. In vitro imaging experiments indicated that miR-29a/b reduce mushroom-shaped dendritic spines on hippocampal neurons with a concomitant increase in filopodial-like outgrowths, suggesting an effect on synapse formation via actin cytoskeleton remodeling. We identified Arpc3, a component of the ARP2/3 actin nucleation complex, as a bona fide target for down-regulation by miR-29a/b. This work provides evidence that targeting of Arpc3 by miR-29a/b fine tunes structural plasticity by regulating actin network branching in mature and developing spines.